Snapshot of a Bacterial Microbiome Shift during the Early Symptoms of a Massive Sponge Die-Off in the Western Mediterranean - Blanquer, Andrea; Uriz, Maria J.; Cebrian, Emma; Galand, Pierre E. (Frontiers in Microbiology, 2016)
Ocean warming is affecting marine benthic ecosystems through mass mortality events that involve marine invertebrates, in particular bivalves, corals, and sponges. Among these events, extensive die-offs of Ircinia fasciculata sponges have been recurrently reported in western Mediterranean. The goal of our study was to test whether the temperature-related mass sponge die-offs were associated with or preceded by an early unbalanced bacterial microbiome in the sponge tissues. We took advantage of the early detection of disease and compared the microbiomes of healthy vs. early diseased I. fasciculata tissues. Our results showed a microbiome shift in early diseased tissues. The abundance of Gammaproteobacteria and Acidobacteria increased and that of Deltaproteobacteria decreased in diseased vs. healthy tissues. The change in community composition was also noticeable at the OTU level. Diseased tissues contained more bacterial sequences previously identified in injured or stressed sponges and corals than healthy tissues. Bacterial diversity increased significantly in diseased tissues, which contained a higher number of low abundance OTUs. Our results do not support the hypothesis of one particular pathogen, whether a Vibrio or any other bacteria, triggering the Northwestern Mediterranean mass mortalities of I. fasciculata. Our data rather suggest an early disruption of the bacterial microbiome balance in healthy sponges through a shift in OTU abundances, and the purported consequent decline of the sponge fitness and resistance to infections. Opportunistic bacteria could colonize the sponge tissues, taking benefit of the sponge weakness, before one or more virulent pathogens might proliferate ending in the mass sponge die-off.